2016
DOI: 10.1111/clr.12909
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the osseointegration of titanium implants incorporating calcium–magnesium: a resonance frequency and histomorphometric analysis in rabbit tibia

Abstract: Within the limitations of this study, the results indicate that the deposition of CaMg on the SLA titanium surface may be effective in enhancing the osseointegration of moderately rough grit-blasted implants by increasing the degree of bone-implant contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
0
18
2
Order By: Relevance
“…Several investigations to improve or accelerate the process of osseointegration have been studied, as well worked on to elaborate new treatments for the surface of the implants (micro topography) with different physical and chemical characteristics [5][6][7][8][9]. These modifications have shown good results, mainly in pre-clinical studies, as reported in the literature [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations to improve or accelerate the process of osseointegration have been studied, as well worked on to elaborate new treatments for the surface of the implants (micro topography) with different physical and chemical characteristics [5][6][7][8][9]. These modifications have shown good results, mainly in pre-clinical studies, as reported in the literature [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Among these surfaces are those coated with nanoparticles and calcium ions [24,25,26]. The incorporation of calcium ions on the surface of a dental implant can in fact stimulate cell attachment, proliferation, alkaline phosphatase activity, and can upregulate gene expression of bone-related proteins [24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, surface treatment with inorganic ions induces a significant roughness modification which is responsible, in turn, of an increased cell adhesion and of a reduced osteoblasts cytotoxicity, as demonstrated in our previous paper 9) . Furthermore, it can be argued that magnesium and calcium addition on test surface plays a pivotal role in promoting and enhancing cell differentiation thus improving bone-implant contact, as supported by the scientific literature 21,22,24) . However the reasons of this outcome still remain unknown and need to be clarified in future studies.…”
Section: Discussionmentioning
confidence: 92%
“…A morphological study of the titanium discs, performed by AFM, reported in our previous work 9) , evidences a nanometric modification of the surface. The innovation of this surface is represented by the surface treatment which create a stable layer on titanium discs able to better promote cell adhesion, as firstly demonstrated by Zizzari et al 9) ,and subsequently by Gehrke et al 24) . In the present work, the goal was to better understand if this surface treatment could also have a positive influence on the differentiation of mesenchymal stem cells towards the osteoblastic lineage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation